Ophthalmomyiasis Caused by Flesh Fly (Dip¬tera: Sarcophagidae) in a Patient with Eye Malignancy in Iran - H Razmjou; Gh Mowlavi; M Nateghpour; S Solaymani-Mohamadi; EB Kia (Tehran University of Medical Sciences, 2007)
Here we describe a case of ophthalmomyiasis in a male patient with basal cell carcinoma. During the operation several live and motile maggots were removed from the lesion. Preliminary examination on the larvae confirmed their affiliation to the genus Sarcophaga (Diptera: Sarcophagidae).This genus is widely distributed throughout the world and species are very difficult to identify. The authors made at¬tempt to approach species identification by rearing larvae to the adult flesh flies, but due to shortage of adult male specimen, reliable diagnosis in the level of species was not obtained. Possible interaction between ocular myiasis and malignancy concerning the case has not been addressed in this paper.